1992
DOI: 10.1007/bf02067317
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated thyroid carcinoma in children and adolescents

Abstract: From 1936 to 1990, 89 children and adolescents (72 girls and 17 boys) were treated for differentiated thyroid carcinoma at the University of Michigan Medical Center; 58 of these patients were first reported in 1971. Thirty (34%) patients had previously received external irradiation to the head and neck, although only 1 (3%) patient of the last 33 patients seen had this history. Patients first presenting from 1971 to 1990 had less advanced disease than those seen earlier. Also, during this time period, the rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
117
2
5

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(131 citation statements)
references
References 5 publications
7
117
2
5
Order By: Relevance
“…Most thyroid cancers in children are papillary (PTC), followed by follicular (FTC) and, more rarely, medullary carcinoma [19,20]. Among Indian studies, Samuel et al found pediatric DTC at a frequency of 30% PTC and 30% mixed papillary and follicular variants [10]; whereas Kumar and Bal reported PTC in 85% of the cases [9].…”
Section: Pathologymentioning
confidence: 99%
“…Most thyroid cancers in children are papillary (PTC), followed by follicular (FTC) and, more rarely, medullary carcinoma [19,20]. Among Indian studies, Samuel et al found pediatric DTC at a frequency of 30% PTC and 30% mixed papillary and follicular variants [10]; whereas Kumar and Bal reported PTC in 85% of the cases [9].…”
Section: Pathologymentioning
confidence: 99%
“…Thyroid carcinoma occurrence is negligible in very young children, although the literature contains isolated clinical cases in 4-6-month-old infants or even neonates (Harness et al 1992, Newman et al 1998, Schlumberger et al 2004a. Age-specific incidence rates diverge for males and females starting at age 10 years, and increase substantially for females from age 13-14 years (Harach & Williams 1995, Bernstein & Gurney 1999 (Fig.…”
Section: Epidemiology Of Juvenile Dtcmentioning
confidence: 99%
“…Studies of large series of thyroid cancer in young children have been largely confined to major tertiary referral centres and have usually concentrated on the clinical behaviour and treatment rather than pathology Rosvoll, 1961, 1970;Buckwalter et al. 1981;Schlumberger et al, 1987;Zimmerman et al, 1988;Harness et al, 1992;Samuel and Sharma, 1991). Thyroid cancer in children is however, currently assuming greater importance, because of the reports of a greatly increased frequency in children exposed to fallout in the areas around Chernobyl (Baverstock et al, 1992;Kazakov et al, 1992;Williams et al, 1993).…”
mentioning
confidence: 99%